PERENCANAAN DAN RANCANGAN ANGGARAN BIAYA PEKERASAN JALAN PERUMAHAN BOGOR KEMANG RESIDENCE BLOK C-7 - Syaiful Syaiful; Aqies Naili Nabila (JPMUJ, 2024)
Street infrastructure is a housing housing facility as health insurance in and out of people. Road conditions greatly affect the comfort and safety of road users. The pavement of the street used by the environmental road is flexible. Flexible pavement is pavement in which the ingredients aggregate and asphalt. Has four layers of basic soil, lower foundations, top foundation, and two layers of surface (layers of bindings and coverings). The TheDurian VII road is 155,8 feet long and 6 feet wide, job plans include a total volume of asphalt of 18,696 square feet and a total area of asphalt of 934,8 square feet, with a finance plan issued during the work of 78.190.072,82 rupiah.